POTENTIAL STUDY OF PHOSPHATE-SOLUBILIZING BACTERIA UNDER DIFFERENT LAND USE IN KAYU TANAM VILAGE, MANDOR DISTRICT, LANDAK REGENCY - Belo, Andreas Nobertus; Nusantara, Rossie Wiedya; Gafur, Sutarman (Jurnal Sains Pertanian Equator, 2025)
Ultisol drylands in West Kalimantan generally have low pH and high concentrations of Al and Fe ions, resulting in phosphorus (P) being less available to plants. Phosphorus is an essential nutrient that supports plant growth and increases crop yield. Phosphorus bound to Al and Fe can be released through the activity of phosphate-solubilizing bacteria (PSB). The presence of PSB is influenced by various factors, including differences in land use. This study aimed to assess the potential and population of PSB under different land uses in Kayu Tanam Village, Mandor District, Landak Regency. The research was conducted from February to April 2025, with analyses carried out at the Soil Biology and Biotechnology Laboratory, Soil Physics Laboratory, and Soil Chemistry and Fertility Laboratory, Faculty of Agriculture, Tanjungpura University. Soil samples were collected from five points arranged diagonally at each site, with 50 m spacing and a depth of 0"“20 cm. Observed parameters included population, potential, and characterization of PSB, soil pH, organic C, available P, total N, C/N ratio, bulk density, soil moisture, and soil temperature. The highest PSB population was found in maize fields (54.60 Ã— 10â¶ CFU/g) with 22 PSB characters. The highest solubilization ability was recorded in isolate Sp22 from secondary forest (solubilization index 7.75), while the lowest was isolate Sp9 from oil palm plantation (index 1.00).